DEVELOPMENT OF METHODOLOGICAL APPROACHES TO THE SELECTION OF MARKETING STRATEGIES IN THE FOREIGN ECONOMIC ACTIVITY OF CHEMICAL ENTERPRISES (Marketing Journal, 2025)
This study focuses on identifying and enhancing the export potential of chemical industry enterprises in Uzbekistan by selecting clearly defined algorithms for the strategic management of their international activities. The article proposes the development of comprehensive programs and projects aimed at bringing chemical products to foreign markets. The research identifies methods for ensuring the adaptability of enterprises to changes in the international environment based on 296 traditional strategic marketing approaches aimed at achieving short -term goals and targeted sales volumes.
Keywords: manufacturing enterprises; international marketing; international trade; marketing strategies; international marketing strategies; product market strategies; diversification; export; China; indicators; indicator assessment; targeted marketing strategies